PERANCANGAN KOMPONEN PRAPABRIKASI RUMAH TINGGAL TUMBUH - Khasani, Makmur (Pendidikan Teknik Bangunan, 2013)
Research to determine: 1) Design the shape and dimensions of the component structures and wall components, 2) the connection form design of each component prapabrikasi; 3) Design and alternative forms of building houses that use results prapabrikasi component design, 4) How to use the results of implementation of housing construction prapabrikasi components. Forms and strategies used in the design are reviewing various existing resources related to building components prapabrikasi home grown and then made a sort of simulation (the drawing), and analyzed the advantages and disadvantages of the design is to get an optimal segment size and shape . The type of data used is, the concept of home grown manufacturing building components, data on innovation prapabrikasi kompoen existing homes, data on the use of building materials prapabrikasi home. Source data obtained from books and supporting literature, direct observation of the realization prapabrikasi home. Based on the design can be concluded: 1) The design of components prapabrikasi namely a) Two-dimensional structure of the type of column length of 30 cm, 30 cm thick and 15 cm high which can be for a variety of high-field, b) the two types of practical column dimensions of length 15 cm, thickness 15 cm and a height of 15 cm, c) three types of beams Sloof (1) length 30 cm, 15 cm thick and 15 cm high (2) length 15 cm, height 15 cm thick 15 cm (3) length of 7.5 cm thick, 12 cm high and 15 cm as locbrick filler that can be used long range beam, c) three-dimensional lockbrick type (1) length 30 cm, 12 cm thick and 15 cm high, (2) a length of 15 cm, 15 cm thick , height 15 cm, (3) length of 7.5 cm, 12 cm thick and 15 cm high as locbrick charger, the components can be used a variety of width and height of the room. 2) The connection between type segment and the other segment types using system male female for easy installation of components so that the segment is made more powerful and binding. 3) alternative design layout, look, cut using a growing residential segment beams, columns, and lockbrick modular, 4) mode of implementation of development sloof beams, ring beams, beam horses lockbrick column and use the assembly in accordance with the scheme of arrangement by the work order and arrange each component and part of it was given a series of reinforcing and strengthening the concrete to strengthen the structure. Keywords: Prapabrikasi, Segment, Beams, Columns, Lockbrick, Modular